TOURISM AND ENVIRONMENT: TOWARD PROMOTING SUSTAINABLE DEVELOPMENT OF TOURISM: A HUMAN RIGHTS PERSPECTIVE - Dharmawan, Ni Ketut Supasti (Indonesia Law Review, 2012)
Tourism activities in era globalization bring positive and negative impacts especially for the host countries destination. To minimize the negative impacts it is very important to always promote the sustainable development of tourism including from a human rights perspective. This paper will discuss concerning who have responsibility to promote a human rights related with sustainable development of tourism. To explore the topic in this article, Author will study both international human rights instruments and environmental convention as well as the soft law regarding the tourism sector such as the UN WTO Global Code Of Ethics. The Law No. 10 Year 2009 concerning Indonesia Tourism Law is also part of legal material studied in this paper. There are national, international legal instruments of the human rights as well as UNWTO Global Codes of Ethics which can be utilized to promote sustainable tourism through human rights perspective. It is considered that all stakeholders have responsibility to promote sustainable development of tourism.